Comparación de actitudes hacia el uso del preservativo en trabajadoras sexuales con y sin diagnóstico de cervicitis en hospital regional docente de Trujillo. 2008 - Cruzado Oyarce, Jesy Carmiña (2010)
This study was conducted at the Hospital Regional Docente de Trujillo in the Reference Center for STI, Trujillo district, province of Trujillo, La Libertad department during June and November 2008 The objective was to compare the attitude towards the use of condoms in sex workers with a diagnosis of cervicitis with those who do not have this diagnosis. The study is prospective, transversal, comparative, in which sex workers were interviewed with and without a diagnosis of cervicitis to compare the attitude towards the use of condoms The results of the study population, are able to take a 90% favorable attitude toward the use of condoms in sex workers diagnosed with cervicitis and a 10% unfavorable, regarding the attitude towards condom use in sex workers without the diagnosis of cervicitis were presented in favor of 97.5% and a negative 2.5%